2014
DOI: 10.1016/j.neuro.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Selenium exposure and depressive symptoms: The Coronary Artery Risk Development in Young Adults Trace Element Study

Abstract: Selenium is an essential trace element important to neurotransmission, but toxic at high levels. Some studies suggest beneficial effects on mood. We assessed the association of selenium exposure with presence of depressive symptoms. Selenium exposure was measured in toenail samples collected in 1987 from 3,735 US participants (age 20–32 years) and depressive symptoms assessed in 1990, 1995, 2000, 2005, and 2010 using the Center for Epidemiologic Studies Depression Scale (CES-D). Binary and polytomous logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Also evidence on the possible effects of Se exposure on depression, cognitive impairment and other psychiatric and neurological diseases, with support for both beneficial and adverse effects of Se under this perspective remaining insufficient and inconsistent [55][56][57]. Interestingly, high exposure to Se in children, as assessed through umbilical cord serum, has been recently linked to an increased risk of attention deficit hyperactivity disorder, a finding which merits further investigation [58].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Also evidence on the possible effects of Se exposure on depression, cognitive impairment and other psychiatric and neurological diseases, with support for both beneficial and adverse effects of Se under this perspective remaining insufficient and inconsistent [55][56][57]. Interestingly, high exposure to Se in children, as assessed through umbilical cord serum, has been recently linked to an increased risk of attention deficit hyperactivity disorder, a finding which merits further investigation [58].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Currently, a marked reassessment of the relation of Se with cancer risk is in progress, since the expectation of a beneficial effect of selenium supplements has vanished [7,8] and indications of an excess risk for skin and prostate cancer [9][10][11][12] have emerged. Such a trend is also occurring for cardiovascular and metabolic diseases [13,14] and neurological and cognitive disorders [15][16][17]. In particular, improvements in the assessment of Se exposure retains a critical position in observational epidemiologic research in order to correctly define its effects on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have tested the association between selenium and depressive symptoms in young adult populations (aged 18-25 y). The one study with the youngest age range of adults aged 20-35 y found that higher, not lower, selenium status was associated with higher risk of depressive symptoms 3 y later (10). Randomized controlled trials (RCTs) have found improvements in mood (11,12) and improvement in postpartum depression (13) with selenium supplementation in adult populations.…”
Section: Introductionmentioning
confidence: 99%
“…Current observational studies focus on older ages and are limited by the methods to determine selenium intake and concentrations. For example, measures of selenium intake may not be reliable because of large variations in the selenium content of foods, which may not be accurately reflected in food composition tables (15), and nail samples tested for selenium reflect long-term selenium exposure; yet, studies using this approach typically measure mood symptoms in the past week (9,10). Past-week mood symptoms may be more closely aligned with an acute measure of selenium, such as serum selenium, rather than a long-term measure of selenium exposure.…”
Section: Introductionmentioning
confidence: 99%